Capillary Driven Transport of Liquid between Parallel Perforated Plates. - Gaulke, Diana (Cuvillier Verlag, 2016)
Of approximation and reduction of termsSolving the differential equation; Experiments; Experimental setup; Capsule; Test cell; Test geometry; Test procedure; Measurement of liquid height and volume; Calculation of liquid height; Determination of mean surface velocity; Experimental and processing uncertainties; Numerics; Software package Flow3D; Representation of solids in Flow3D; Calculation of the surface of fluids; Basic fluid flow equations; Boundary conditions; Numerical calculation of the experimental set-up; Grid and boundary conditions; Initial and closing conditions.